Assessment of Lake Tourism Object as Ecotourism Destination in Merabu, Berau Regency, East Kalimantan - Iin Sumbada Sulistyorini; Jerlita Kadang Allo; Muli Edwin; Rosdianto (Jurnal Sylva Lestari, 2022)
Nya'deng Lake, also called the blue lake, is located in the Sangkulirang Mangkaliat Karst landscape area and is included in the Merabu Village Forest area. Natural lakes with certain uniqueness and characteristics as Nya'deng Lake have become a tourist attraction in Indonesia. Therefore, assessing natural tourism in the lake is very important to develop environmentally friendly and responsible tourism. This research was conducted to explore and assess the potential of Nya'deng Lake as a lake tourism site. The study used a qualitative descriptive approach using a scoring method. Based on field observation, Nya;deng Lake is unique in terms of beauty, comfort, variety of activities, and environmental cleanliness. There are also other interesting objects such as tree houses and gazebos surrounding the lakeside. The results showed that the natural tourism object in Nya'deng Lake has very high criteria; hence it is very feasible to be developed as an ecotourism destination. The ecotourism development of Nya'deng Lake should follow the principles of sustainability and conservation because it is a protected geological area with prehistoric, cultural, and unique natural ecosystem values. Keywords: blue lake, ecotourism Merabu Village Forest, Nya'deng Lake